Milk lipid composition is modified by perinatal exposure to bisphenol A - Altamirano, Gabriela Anahí (2015)
To evaluate whether bisphenol A (BPA) modifies the synthesis, composition and/or profile of fatty acids (FAs) in the mammary glands of perinatally exposed animals, pregnant rats were orally exposed to 0, 0.6 or 52 µg BPA/kg/day from gestation day (GD) 9 until weaning. F1 females were bred, and on GD21, lactation day 2 (LD2) and LD10, mammary glands were obtained. On LD10, milk samples were collected, and FA profiles and lipid compositions were established. On GD21 and LD2, BPA exposure delayed mammary alveolar maturation and modified the synthesis of milk fat globules. On LD10, mammary gland histo-architecture was restored; however, the milk of BPA-exposed F1 dams had a FA profile and lipid concentration different from those of the control milk. Furthermore, the body weight gain of BPA52 F2 pups was increased compared with control animals. Thus, perinatal exposure to BPA modifies milk quality, compromising the normal growth of offspring.